Pemanfaatan Sosial Media Sebagai Bentuk Inovasi, Strategi Komunikasi dan Kreatifitas Layanan di Perpustakaan Perguruan Tinggi - Utomo, Endhar Priyo (IAIN Curup, 2019)
Nowadays social media has become a lifestyle of some Indonesian people and libraries as one of the institutions that provide information services and providers of information sources for users. In addition to the phenomenon of the use of social media as mentioned above, in several studies on the use of social media in libraries it was found that at present there has begun to be growing awareness from libraries to use social media as a form of innovation from services provided by libraries to visitors. In this study trying to analyze the use of social media as a form of innovation, communication strategies and service creativity in the college library. The method used is descriptive analysis. In order for the use of social media in the library to be more optimal, there are several things that must be considered. Optimizing the use of social media in libraries needs to be done so that all available information can be conveyed properly.